(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The development of social competencies in future teachers is crucial in an innovative educational environment, where teaching methods, technological integration, and diverse student populations continuously reshape the classroom dynamics. This article explores the relevance of social competencies, such as emotional intelligence, communication, conflict resolution, and cultural awareness, in enhancing the effectiveness of teaching. In the context of modern education, these competencies enable teachers to build positive relationships, foster inclusive learning environments, and adapt to the evolving challenges of the profession. Effective teacher preparation programs must integrate social competency development to ensure that future educators are well-equipped for contemporary educational demands.